Optimizing Assessment Techniques for Students with Diverse Special Needs in Schools - Fathoni, Arifuddin; Sutimin, Leo Agung; Sumaryanti, Sri (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
This study investigates effective assessment techniques for students with diverse special needs in school settings. Background research highlights the importance of individualized assessment strategies to ensure equitable education opportunities. The study aims to identify optimal methods and practices that enhance the evaluation process for these students. The research utilizes a mixed-methods approach, combining qualitative and quantitative data from observations, surveys, and interviews with educators and specialists. Analysis focuses on assessing different techniques' impact on student engagement, academic performance, and adaptive skills. Findings indicate that tailored assessments, incorporating a variety of methods such as adaptive testing and alternative response formats, significantly benefit students with special needs. These techniques enhance understanding and provide actionable insights for personalized education plans. The study concludes that a multifaceted approach to assessing students with special needs is essential for their success. Emphasizing the implementation of individualized assessment practices can lead to more inclusive and effective educational experiences. Readers are encouraged to consider the potential benefits of adapting their assessment methods to better support diverse learning needs.